A Novel Infrared Temperature Measurement with Dual Mode Modulation of Thermopile Sensor - Chih-Hsiung Shen; Shu-Jung Chen; Yi-Ting Guo (Sensors, 2019)
Superior to the traditional infrared temperature sensing architecture including infrared sensor and thermistor, we propose a novel sensing approach based on a single thermopile sensor with dual modes modulation. A switching and sensing circuit is proposed and realized with a chopper amplifier AD8551 and p-channel MOSFET (PMOS) for switching between detection of thermal radiation and the target and the ambient temperature for compensation. The error of target temperature after temperature compensation is estimated at less than 0.14 °C.